COMPATIBILITY STUDY OF TRICHODERMA SPECIES WITH NEWER FUNGICIDES AND ITS EFFECT ON SOIL BORNE PATHOGENS (Journal of Plant Disease Sciences, 2025)
Based on their ability to suppress plant pathogens and enhance nutrient uptake by plants, Trichoderma spp. are widely known as effective biocontrol agents. The present investigation was undertaken to study the compatibility of four Trichoderma species, namely Trichoderma harzianum, Trichoderma asperellum, Trichoderma koningii and Trichoderma hamatum, with five commonly used fungicides. The fungicides tested were Thiophanate methyl + Pyraclostrobin, Carbendazim + Mancozeb, Carboxin + Thiram, Metalaxyl + Mancozeb and Tebuconazole. Each fungicide was evaluated at three concentrations, viz. recommended dose, 50% of recommended dose and 25% of recommended dose.The results revealed that mycelial growth of Trichoderma spp. was affected differently by the fungicides at various concentrations. Among the fungicides tested, Metalaxyl + Mancozeb was found to be compatible with all four Trichoderma species, showing the least inhibition at 25% of the recommended dose (0.05% concentration). The remaining four fungicides exhibited incompatibility with all Trichoderma isolates at all three concentrations tested. Carbendazim + Mancozeb and Tebuconazole caused complete (100%) inhibition of all Trichoderma spp. at all doses. Among the tested biocontrol agents, Trichoderma asperellum and Trichoderma harzianum were found to be more effective against soil-borne pathogens such as Rhizoctonia bataticola, Fusarium oxysporum and Sclerotium rolfsii. The study highlights the importance of selecting compatible fungicide–biocontrol combinations for integrated disease management strategies.
Keywords: Compatibility, Fungicides, soilborne, Trichoderma